Numerical Simulation of Density Current Evolution in a Diverging Channel - Mitra Javan; Afshin Eghbalzadeh; Masoud Montazeri Namin (Advances in Civil Engineering)
When a buoyant inflow of higher density enters a reservoir, it sinks below the ambient water and forms an underflow. Downstream of the plunge point, the flow becomes progressively diluted due to the fluid entrainment. This study seeks to explore the ability of 2D width-averaged unsteady Reynolds-averaged Navier-Stokes (RANS) simulation approach for resolving density currents in an inclined diverging channel. 2D width-averaged unsteady RANS equations closed by a buoyancy-modified 𝑘−𝜀 turbulence model are integrated in time with a second-order fractional step approach coupled with a direct implicit method and discretized in space on a staggered mesh using a second-order accurate finite volume approach incorporating a high-resolution semi-Lagrangian technique for the convective terms. A series of 2D width-averaged unsteady simulations is carried out for density currents. Comparisons with the experimental measurements and the other numerical simulations show that the predictions of velocity and density field are with reasonable accuracy.